Impact of Baseline and Trajectory of Triglyceride-Glucose Index on Cardiovascular Outcomes in Patients With Type 2 Diabetes Mellitus - Tai, Shi; Fu, Liyao; Zhang, Ningjie; Zhou, Ying; Xing, Zhenhua; Wang, Yongjun (Frontiers in Endocrinology, 2022)
Background and aims: This study aimed to evaluate the association of the triglyceride-glucose (TyG) index with the cardiovascular incidence in patients with type 2 diabetes mellitus (T2DM). Methods and results: Secondary analysis in patients with long-lasting T2DM from the Action to Control Cardiovascular Risk in Diabetes study was performed. The primary outcome was the first occurrence of major adverse cardiovascular events (MACEs). The association between the baseline and trajectories of the TyG index and MACEs was evaluated by Cox proportional hazards regression analysis. During a median follow-up period of 8.8 years, 1,815 (17.8%) patients developed MACEs. After traditional cardiovascular risk factor adjustments, each 1-standard deviation increase in the TyG index was associated with a 19.00% higher MACE risk, similar to that in the TyG index quartile characterization. Four distinct trajectories of TyG indexes were identified: low (16.17%), moderate (40.01%), high (34.60%), and very high (9.30%). In multivariate analysis, high and very high TyG index trajectories showed a greater risk of future MACE incidence than the low TyG index trajectory. A similar association was observed between the TyG index and the occurrence of coronary heart disease. Conclusions: The baseline and trajectories of the TyG index were significantly associated with the occurrence of MACEs in patients with T2DM.